PELECEHAN TERHADAP PEREMPUAN DALAM MEME - Herry Nur Hidayat; Tienn Immerry (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The rapid spread of a meme thought to influence both individual and social behavior. The meme uses symbols to convey ideas and ideas. In practice, memes are also used as a means of patriarchal power legitimation through symbolic violence. Through the processing of language and images into symbols, memes are thought to be a tool of men's legitimacy. This article discusses several forms of content of harassment against women in the form of internet memes. First, the memes are analyzed by grasping the meaning of the symbols in them using semiotics' theory. Then, using Pierre Bourdieu's symbolic violence theory: habitus, capital, arenas, and symbolic violence, memes are analyzed to find the factors that cause the appearance of memes with the content of harassment against women. The results indicate that stereotype, gender bias, and mental structure are habitus structure which plays an essential role so that symbolic violence becomes natural for its victims. The internet, as an arena, has become the initial capital for men to dominate. Also, naming and mentioning are forms of symbolic violence against women by forming certain boundaries and categories.